2021
DOI: 10.1111/jwip.12203
|View full text |Cite
|
Sign up to set email alerts
|

Institutional incongruence and unauthorized copying in Poland

Abstract: The aim of this article was to find out how the cognitive dissonance resulting from the occurrence of institutional incongruence in the context of copying information goods in online society is reduced. The implementation of this goal required conceptualization work and empirical research. The conceptual part was based on the theory of cognitive dissonance by Festinger as well as works on the concept of institutional congruence. The essence of the conceptualization work was the formulation of the concept of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As a result, the law may be reinterpreted so that it does not overtly contradict informal institutions. This is confirmed, for example, by Czetwertyński's (2022) research on copyright enforcement and oline piracy. On the other hand, in the third and fourth cases, depending on the relationship (hierarchy) between laws, some national formal institutions may be transformed (if inconsistencies are observed and effectively reported), which may or may not be compatible with national informal institutions and/or with other national formal institutions, and, consequently, these changes may lead to a reduction/increase in the disruption of the institutional system.…”
Section: Disruption Of the Institutional Systemsupporting
confidence: 52%
“…As a result, the law may be reinterpreted so that it does not overtly contradict informal institutions. This is confirmed, for example, by Czetwertyński's (2022) research on copyright enforcement and oline piracy. On the other hand, in the third and fourth cases, depending on the relationship (hierarchy) between laws, some national formal institutions may be transformed (if inconsistencies are observed and effectively reported), which may or may not be compatible with national informal institutions and/or with other national formal institutions, and, consequently, these changes may lead to a reduction/increase in the disruption of the institutional system.…”
Section: Disruption Of the Institutional Systemsupporting
confidence: 52%
“…To express this in a very colloquial and simplistic way -in specific cases the copier does not violate copyright, but the person who makes the work available for copying does. As a result, the very nature of copyright is complicated, and the average respondent has not studied copyright law in detail at any stage of their life (Czetwertyński, 2022). The second problem with determining the level of piracy is comparing survey data and contrasting them in terms of the legality of various practices.…”
Section: Methodsmentioning
confidence: 99%
“…In their research, they used the EFA method, and the factor related to knowledge of copyright law can be considered alarming. Similarly, in a study by Czetwertyński (2022), on the level of piracy in general, EFA analysis provided some reason to conclude that the knowledge of copyright law among Poles is poor. Interestingly, the study showed that respondents were not so much unaware of what was prohibited, but rather unaware of what was allowed.…”
Section: Literature Reviewmentioning
confidence: 96%